EFFECTIVE STRATEGIES IN HUMAN RESOURCE MANAGEMENT - Loso Judijanto; Benediktus Rolando (CV. Adiba Aisha Amira, 2024)
Effective human resource management is the key to building and maintaining an organisation's competitive advantage. The research method used is literature. The results show that the integration of these strategies not only strengthens internal operations, but also improves employee well-being and organisational innovation. This research recommends the implementation of a holistic approach to HR management as an essential step for success in a dynamic and competitive business ecosystem.